2012
DOI: 10.1155/2012/893275
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Genotyping and E6/E7 mRNA Expression in Greek Women with Intraepithelial Neoplasia and Squamous Cell Carcinoma of the Vagina and Vulva

Abstract: A large proportion of vaginal and vulvar squamous cell carcinomas (SCCs) and intraepithelial neoplasias (VAIN and VIN) are associated with HPV infection, mainly type 16. The purpose of this study was to identify HPV genotypes, as well as E6/E7 mRNA expression of high-risk HPVs (16, 18, 31, 33, and 45) in 56 histology samples of VAIN, VIN, vaginal, and vulvar SCCs. HPV was identified in 56% of VAIN and 50% of vaginal SCCs, 71.4% of VIN and 50% of vulvar SCCs. E6/E7 mRNA expression was found in one-third of VAIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…Two studies looked at women with vaginal and/or vulvar intraepithelial neoplasia or cancer (Tables 3,4) (Anastasiadis et al, 2000; Tsimplaki et al, 2012). Both studies were limited because of the small and non-random population, as well as the fact that HPV testing methods were not documented in the paper.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies looked at women with vaginal and/or vulvar intraepithelial neoplasia or cancer (Tables 3,4) (Anastasiadis et al, 2000; Tsimplaki et al, 2012). Both studies were limited because of the small and non-random population, as well as the fact that HPV testing methods were not documented in the paper.…”
Section: Resultsmentioning
confidence: 99%
“…Hence we are not confident in the prevalence rates reported. Only one of these studies looked at age as an independent risk factor for HPV infection and found that younger women with vulvar or vaginal neoplasia were at a higher risk for HPV infection (Tsimplaki, et al, 2012). …”
Section: Resultsmentioning
confidence: 99%
“…reporting 100% HPV positivity, 40 out of 44 VaIN patients had a history of cervical carcinoma, which is known to be associated with persistent high‐risk HPV infection . In contrast, Tsimplaki et al . found a prevalence of 56% in VaIN among women with no history of other HPV‐associated malignancies.…”
Section: Discussionmentioning
confidence: 95%
“…Squamous cell vaginal carcinoma shares some risk factors with cervical carcinoma, including a strong relationship with high-risk human papilloma viruses [HPV]s, and especially with HPV-16 [29][30][31][32][33][34][35][36][37]. In a US population-based case-control study, the women with vaginal cancer were more likely to have five or more lifetime sexual partners (odds ratio [OR] = 3.1, 95% confidence interval [CI] = 1.9-4.9), to have an early age at first intercourse (<17 years, OR = 2.0, 95% CI = 1.2-3.5), and to be current smokers at diagnosis (OR = 2.1, 95% CI = 1.4-3.1) when compared with controls [29].…”
Section: Epidemiology Risk Factors and Natural Historymentioning
confidence: 99%